Perbandingan Turnaround Time Antara Verifikasi Manual dan Verifikasi Otomatis terhadap Hasil Pemeriksaan Profil Lipid di Laboratorium Klinik Pramita Cabang Pajajaran Kota Bandung - Barrianti Barrianti; Kafesa Ally; Yumanah Siti (Syntax Corporation, 2023)
Turnaround Time (TAT) for laboratory services is an indicator of the quality of laboratory services to meet customer satisfaction and as a benchmark for laboratory performance. Laboratory results are very important to be delivered in the shortest possible time for the rapid diagnosis and management of patients. One of the factors that causes the length of TAT in the reporting process at the analytical stage is the verification process of inspection results which is still carried out manually by ATLM personnel. Implementing automatic verification of examination results is one way to overcome the long waiting time (TAT) for laboratory services. The aim of this research is to determinate the TAT of manual verification and automatic verification of lipid profile examination results, and testing the difference in TAT between manual verification and automatic verification of lipid profile examination results at the analytical stage at the Pramita clinical laboratory, Pajajaran branch in Bandung city. The method used in this research is to use descriptive comparative method with a quantitative approach. Based on the research that has been done, the average ± standard deviation TAT for manual verification of the results of lipid profile examination was 112.44 ± 46.02 minutes, while the automatic verification TAT was 68.03 ± 28.07 minutes. The results of the independent sample t-test between TAT manual verification and automatic verification of the lipid profile examination results with a significance value of Sig.(2-tailed) 0.000 <0.05. The conclusion of this research is that TAT verification of lipid profile examination results at the analytical stage decreased after automatic verification was implemented. There is a significant difference in Turnaround Time between manual verification and automatic verification of the results of lipid profile examinations at the analytical stage at the Pramita Clinical Laboratory, Pajajaran branch in Bandung city.